A community study on the impacts of Covid-19 with respect to individual psychological well-being - Tavano Blessi, Giorgio; Grossi, Enzo; Colleoni, Matteo (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2025)
The present work therefore aims to explore the possible impacts caused by the Covid-19 pandemic with respect to individual psychological well-being through a survey conducted in February 2020, and repeated one year later, February 2021, on a sample of the population of a municipality in the Milan metropolitan area, Baranzate. The research is oriented in the strand of community studies, and through the comparison of the two survey waves, aims to highlight the possible changes that have occurred with respect to the main determinants that make up individual psychological well-being, and the possible influence of the socio-cultural activities on the aformetioned dimension.